Controlled synthesis of anisotropic hexagonal boron nitride nano-web. (1st August 2017) - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Shah, Syed Tawab; Rehman, Fida; Khan, Ghulamullah; Muhammad, Nawshad; Rehman, Muhammad Abdur; Khan, Amir Sada; Ahmed, Syed Muzamil; Gulzar, Mubashir; Numan, Arshid; Ali, Hazrat
Abstract: The assembly of one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) nanomaterial show entirely different properties than their individual counterparts. Since the shape of nanomaterials plays a crucial role in designing devices with desired applications, relentless efforts are on-going to obtain the parameters for controlling the shape of the final product. Present study concerns the synthesis and growth of a combined 2D and 3D structure of Hexagonal Boron Nitride Nanofibers Web (BNNFs-Web) from 1D structure of BNNFs. Magnesium catalytic layer deposited on Silicon substrate produces Web-like nucleation sites when etches with NH3 flow at 300 °C. The precursor's mixture of B, γ-Fe2 O3 and MgO annealed at 500 °C uses these nucleation sites as a pattern, and grow BNNFs-Web in a unique 2D and 3D configuration at 1000 °C. XRD, Raman and FTIR spectroscopies confirmed the h-BN phase of the as-synthesized BNNFs-Web. This unique 2D and 3D material can offer distinguish features with improved properties as compared to other nanostructures of h-BN. Such a material can be a much better choice for its potential applications in different fields of bio-medical, microelectronic mechanical system and solid state neutron detectors. Graphical abstract: Synopsis: The precursor's mixture at higher temperature synthesizes BNNFs vapors. These vapors at 1000 °C deposit in web-like nucleation sites produced in Mg catalytic layer deposited on Silicon substrate. After super-saturation, a combined 2D and 3D structure of BNNFs-Web grows at the top of the substrate following the nucleation sites as a pattern.